Effect of different microbial inoculants on morphological and fruit characteristics of strawberry (Fragaria × ananassa) cv. winter dawn - SINGH, GURPREM; BISHNOI, CHETAK; SINGH, NAVPREM; PANDOVE, GULAB; BISHNOI, SUDHA (The Indian Journal of Agricultural Sciences, 2024)
In the rhizosphere, plants interact with a wide range of microorganisms that play crucial role in several aspects of plant development and defence against biotic and abiotic stresses. The present study was carried out during 2022–23 at Regional Research Station (Punjab Agricultural University, Ludhiana), Bathinda, Punjab to elucidate the role of various microbial inoculants on vegetative growth, yield, and quality of strawberry (Fragaria × ananassa). The results depicted that, strawberry plants treated with Burkholderia seminalis + Stenotrophomonas maltophilia + VAM + PAU consortium (T10) was found best over the control in terms of morphological characteristics, viz. plant height, spread, leaf area, number of leaves, crown diameter, and root characteristics of plant. Fruit characteristics like fruit weight, fruit length, and fruit diameter were improved by inoculating the plants with Burkholderia seminalis + Stenotrophomonas maltophilia + VAM + PAU consortium. The cumulative marketable yield of both strawberry cultivar winter dawn was enhanced by inoculating the plant with different microbial inoculants but found maximum in Burkholderia seminalis + Stenotrophomonas maltophilia + VAM + PAU consortium.